Lessons from the macroinvertebrates: species‐genetic diversity correlations highlight important dissimilar relationships. (November 2016) - Seymour, Mathew; Seppälä, Katri; Mächler, Elvira; Altermatt, Florian
Summary: Species and genetic diversity patterns are predicted to co‐vary due to similar mechanistic processes. Previous studies assessing species and genetic diversity correlations (SGDCs) have focused primarily on local diversity patterns or island‐like systems and ignore the underlying dispersal network. Here we assessed local and regional SGDCs using freshwater macroinvertebrates sampled across the Rhine river network, a spatially large and highly connected system, in Switzerland. We utilised a set of polymorphic microsatellite markers to assess the genetic diversity of two amphipod species of the Gammarus fossarum complex, which were compared to species level diversities of Amphipoda, Ephemeroptera, Plecoptera, Trichoptera and family level macroinvertebrate diversity across 217 randomly selected sites. All sites were selected based on a representative and standardised species‐sampling scheme. We analysed within site (α‐SGDC) and between‐site SGDC (β‐SGDC). Against our expectation, we generally found negative or null α‐SGDCs and β‐SGDCs. However, we did find genetic diversity to be spatially structured, whereas species richness was related to local environmental factors. These findings suggest that the genetic and species levels of diversity observed are driven by different mechanisms (e.g., environment versus demography), or operate across different temporal or spatial scales (e.g., colonisation history or dendritic river network structure), and may be attributed to differences in the species' ecology or life history. Overall, conservation measures in riverine systems aiming at only one level of diversity may not necessarily benefit other levels of diversity.